DNA-methylation in C1R is a prognostic biomarker for acute myeloid leukemia. Issue 1 (December 2015) - Božić, Tanja; Lin, Qiong; Frobel, Joana; Wilop, Stefan; Hoffmann, Melanie; Müller-Tidow, Carsten; Brümmendorf, Tim; Jost, Edgar; Wagner, Wolfgang
Abstract Background Epigenetic aberrations play a central role in the pathophysiology of acute myeloid leukemia (AML). It has been shown that molecular signatures based on DNA-methylation (DNAm) patterns can be used for classification of the disease. In this study, we followed the hypothesis that DNAm at a single CpG site might support risk stratification in AML. Findings Using DNAm profiles of 194 patients from The Cancer Genome Atlas (TCGA), we identified a CpG site in complement component 1 subcomponent R (C1R ) as best suited biomarker: patients with higher methylation at this CpG site (>27 % DNAm) reveal significantly longer overall survival (53 versus 11 months;P < 0.0001). This finding was validated in an independent set of 62 DNAm profiles of cytogenetically normal AML patients (P = 0.009) and with a region-specific pyrosequencing assay in 84 AML samples (P = 0.012). DNAm ofC1R correlated with genomic DNAm and gene expression patterns, whereas there was only moderate association with gene expression levels ofC1R . These results indicate that DNAm ofC1R is a biomarker reflecting chromatin reorganization rather than being of pathophysiological relevance per se. Notably, DNAm ofC1R was associated with occurrence of specific genomic mutations that are traditionally used for risk stratification in AML. Furthermore, DNAm ofC1R correlates also with overall survival in several other types of cancer, but the prognostic relevance was less pronounced than in AML. Conclusions Analysis of DNAm atC1R provides a simple, robust, and cost-effective biomarker to further complement risk assessment in AML.